Learner Perception on Blended Learning: Moderating Role of Technology - Shahi, Amrit (Journal of Entrepreneurship & Management Studies, 2025)
This study explores the impact of blended learning (BL) on academic performance and literacy skills among university students in Nepal, emphasizing the moderating role of technology access and digital proficiency. Anchored in the Community of Inquiry (COI) framework, the research examines how cognitive, social, and teaching presences enhance learning outcomes in digitally enabled environments. A pre-post quantitative design was employed over a 15-week semester involving 54 students from various academic years and disciplines. Data were collected via structured surveys and institutional grade records, measuring reading comprehension, writing fluency, and BL perceptions. Statistical analyses – including paired t-tests, ANOVA, correlation, and regression – showed that BL significantly improved literacy skills and academic achievement (p < 0.001). Strong positive correlations were found between students’ perceptions of BL and both academic performance and literacy development (r > 0.99). Technology access and digital readiness were significant predictors of favorable BL experiences. Third-year students demonstrated the greatest improvements, highlighting the role of cumulative digital exposure. Despite promising results, limitations such as a small sample size, self-reported data, and context specificity constrain generalizability. The study underscores the need for robust digital infrastructure, inclusive policies, and capacity-building initiatives in higher education. It advocates for the strategic implementation of blended learning to bridge educational inequities and improve learning outcomes in resource-constrained settings.